АБАЙ ШЫҒАРМАЛАРЫНДА ИЛИМ-БИЛИМ МӘСЕЛЕЛЕРИНИҢ СӘЎЛЕЛЕНИЎИ - Давлетов, Б.А. (FAN va JAMIYAT, 2025)
The article discusses the didactic poems of the classic poet of Kazakh literature, Abay Kunanbayuly. The poet’s poetry explored issues of wisdom, knowledge acquisition, and upbringing. Works celebrating the future destiny of the nation, human greatness, human qualities, and the issues of diligence and education were discussed with examples.